Structural, optical and biological characterization of a new cobalt-based mixed halide hybrid compound: insights from DFT and vibrational analysis - Iteb Ben Mahmoud; Naoufel Ben Hamadi; Sandra Walha; Nourhene Zammel; Ali Ben Ahmed; Ahlem Guesmi; Wesam Abd El-Fattah; Ferdinando Costantino; Houcine Naïli (Royal Society Open Science, 2025)
A novel cobalt-based hybrid compound, bis(4-dimethylaminopyridinium)bromo-chlorocobaltate(II) (C7H11N2)2[CoBr2.28Cl1.72] (1), was successfully synthesized via a slow evaporation method at room temperature. The crystalline material was thoroughly characterized using single-crystal X-ray diffraction, Hirshfeld surface analysis, Fourier transform infrared (FT-IR) and Raman spectroscopy, UV–Vis optical absorption, thermal analysis and theoretical density functional theory (DFT) calculations. Crystallographic analysis revealed that compound (1) crystallizes in the centrosymmetric monoclinic space group C2/c, featuring discrete [CoBr2.28Cl1.72]2- anions and protonated amine cations (C₇H₁₁N₂)+. These units are interconnected via an extensive network of N–H···Br/Cl and C–H···Br/Cl hydrogen bonds, stabilizing the crystal lattice. Thermal analysis indicated a significant phase transition at approximately 203°C, underscoring the thermal responsiveness of the structure. Spectroscopic techniques highlighted the vibrational characteristics of key functional groups, and DFT calculations offered further insights into electronic and structural properties. Biological evaluation demonstrated that compound (1) possesses notable antimicrobial activity, particularly against Escherichia coli, Staphylococcus aureus and Bacillus subtilis, with inhibition zones ranging from moderate to strong depending on the microorganism tested. Additionally, the compound exhibited promising antioxidant capacity in 1,1-diphenyl-2-picrylhydrazyl (DPPH) assays, moderate α-amylase inhibition indicative of anti-diabetic potential and measurable anti-inflammatory effects. These findings suggest that compound (1) is a multifunctional material with potential applications in biomedical and pharmaceutical fields.